PEMBERDAYAAN SUMBER DAYA APARAT DESA (Study kasus di Desa Kuyanga Kecamatan Tombatu Utara Kabupaten Minahasa Tenggara ) - LILIPORY, PRICILIA; POSUMAH, JOHNNY HANNY; MAMBO, RULLY (Sam Ratulangi University, 2018)
This research will reveal how the empowerment of village apparatus resource in Kuyanga is caused by not yetoptimal service given by village government apparatus.Research method applied in this research is qualitative research method intend to get a clear picture aboutEmpowerment of Resource of Kuyanga Village Apparatus. Sources of data or informants in this study weretaken from various elements covered as apparatus of Kuyanga Village with data collection techniques usedInterview, Observation and DocumentationBased on research empowerment of government apparatus of Kuyanga Village have good seen fromindependence in solving existing problems in society. Village officials are quick to respond and have goodresponsibilitas to address the circumstances surrounding. Kuyanga village officials were agile and proactiveenough to respond to complaintsKeywords: Empowerment, Apparatus Resources, and Village